Identifikasi Metabolit Sekunder Ekstrak Metanol Akar dan Batang Merung (Coptosapelta tomentosa ) yang Memiliki Aktivitas Antioksidan Menggunakan Metode KLT Autografi - Wahyu; Angga; Nurul Yasmin (Proceeding of Mulawarman Pharmaceuticals Conferences, 2019)
Secondary metabolites produced by plants have been known to have a variety of biological activities including antioxidants that serve to ward off oxidant compounds and free radicals. The roots of merung (Coptosapelta tomentosa) has been known to have strong activity as an antioxidant while antioxidant activity in the stem is not yet known to date. This research aims to determine the secondary metabolites that have antioxidant activity on the root extracts and the stem of the vines qualitatively. The root extract and the stem of the merung plant are extracted with a methanol solvent using the maceration method. Antioxidant activity and identification of secondary metabolites are carried out qualitatively by the method of autography using the 2.2-Diphenyl-1-Picrylhydrazyl compound (DPPH) and some reagents of the secondary metabolite. Antioxidant activity of the merung root extract is on spot with RF 0.08 and 0.66. Spot with the RF 0.66 shows the brown color when reacted FeCl3, fluorescent yellow in UV rays 254 and 366 nm after reacted AlCl3 and red when reacted with KOH. The antioxidant activity of the merung stem extracts is at Rf 0.16, 0.33, 0.58, 0.66, and 0.75. Spot with the Rf 0.16 shows the color of brown when reacted FeCl3 and fluorescent blue in UV rays 254 and 366 nm after reacted AlCl3. Secondary metabolites that have antioxidant activity on root extracts and stems are suspected to be derivative phenolic compounds derived from flavonoid compounds.